Study of sediment discharge in the Marina Bay catchment - Yeo, Alex Soon Tat. (2009)
An estuarine system is a semi-enclosed area with one or more channels of water leading to it, and at the same time, is connected to the open sea. It gives a natural protection against suspended sediments, and it prevents it from entering the estuary. This protection is mainly due to the salinity of the water. When the water has a higher concentration of salinity, the sediments tend to form larger flocs with greater ease. As the flocs are large, the duration of the settlement of the flocs tends to be shorter. When the water in the Marina Bay turns fresh, the low salinity causes the flocs to be smaller, and does not settle quickly enough. Thus, these flocs sediment will be transported into the barrage. The main objective is to find out exactly how much sediment there would be in the estuary due to the freshwater.